Identification of Panax spp. in the Northern Vietnam based on ITS-rDNA sequence analysis - Viet Thanh, Tran Thi; Ngoc Bon, Trinh; Van Truong, Do; Quang Tuyen, Pham; Van Luong, Hua; Van The, Pham; Ke Long, Phan (Vietnam Journal of Biotechnology, 2022)
In order to accurately identify ginseng species (Panax spp.) that grow naturally in some Northern provinces of Vietnam, we collected 30 natural ginseng samples and used nuclear genetic region (ITS-rDNA) for current analysis. The success rate for nuclear genomic region PCR (ITS-rDNA) amplification is 100%. The bidirectional sequence read success rate obtained from the PCR product was 100%, with a nucleotide sequence length of 588 bp. Based on the analysis of ITS-rDNA region results, the samples of ginseng species from Tuyen Quang and Cao Bang provinces have a close relationship with Panax notoginseng (MLBS = 100%), while the samples of ginseng species from Ha Giang and Yen Bai provinces have a close relationship with P. stipuleanatus (MLBS = 99%). As the results, the ginseng samples from Tuyen Quang and Cao Bang provinces were identified as Panax notoginseng and the ginseng samples from Ha Giang and Yen Bai provinces were identified as Panax stipuleanatus. The obtained result also recorded new distribution areas of P. notoginseng in Tuyen Quang and Cao Bang provinces. Furthermore, we successfully registered the nuclear nucleotide sequences of these two Panax species on GenBank with 24 codes (from OM190408 to OM190410, from OM213014 to OM213030, and from OK376138 to OK376141).